The design and implementation of a Fortran-77 to Modula-2 translator - Myhr, Eric Robert (1990)
Thesis (M.Sc.)--Memorial University of Newfoundland, 1990. Computer Science Bibliography: leaves 124-127. A source-to-source translator is a program which translates programs written in a given high-level programming language into another high-level language. They provide a reliable means for the re-use, sharing, and development of software. -- In this thesis, the design and implementation of a source-to-source translator which converts Fortran-77 programs into semantically 'equivalent’ Modula-2 programs is described. - An attribute grammar is used to formally describe the translation. Attribute grammars are typically used in the specification of compilers and translators, and describe translation in a syntax-directed fashion. -- The translator was generated from the attribute grammar using the GAG system, a translator/compiler writing system based on attribute grammars. Attributed parse trees are used for the intermediate representation of the syntax and semantics of Fortran programs during translation. -- Keywords: source-to-source translation; program transformation, attribute grammars, translator-writing systems,the GAG system, programming languages, Fortran-77, Modula-2.